Photorelease of phosphates: Mild methods for protecting phosphate derivatives - Senadheera, Sanjeewa N.; Yousef, Abraham L.; Givens, Richard S. (Beilstein Journal of Organic Chemistry, 2014)
We have developed a new photoremovable protecting group for caging phosphates in the near UV. Diethyl 2-(4-hydroxy-1-naphthyl)-2-oxoethyl phosphate (14a) quantitatively releases diethyl phosphate upon irradiation in aq MeOH or aq MeCN at 350 nm, with quantum efficiencies ranging from 0.021 to 0.067 depending on the solvent composition. The deprotection reactions originate from the triplet excited state, are robust under ambient conditions and can be carried on to 100% conversion. Similar results were found with diethyl 2-(4-methoxy-1-naphthyl)-2-oxoethyl phosphate (14b), although it was significantly less efficient compared with 14a. A key step in the deprotection reaction in aq MeOH is considered to be a Favorskii rearrangement of the naphthyl ketone motif of 14a,b to naphthylacetate esters 25 and 26. Disruption of the ketone-naphthyl ring conjugation significantly shifts the photoproduct absorption away from the effective incident wavelength for decaging of 14, driving the reaction to completion. The Favorskii rearrangement does not occur in aqueous acetonitrile although diethyl phosphate is released. Other substitution patterns on the naphthyl or quinolin-5-yl core, such as the 2,6-naphthyl 10 or 8-benzyloxyquinolin-5-yl 24 platforms, also do not rearrange by aryl migration upon photolysis and, therefore, do not proceed to completion. The 2,6-naphthyl ketone platform instead remains intact whereas the quinolin-5-yl ketone fragments to a much more complex, highly absorbing reaction mixture that competes for the incident light.
Keywords: caged phosphates; hydroxynaphthylacetyl; organophosphorus; photo-Favorskii rearrangement; photoremovable protecting groups